The beautiful fall : fashion, genius, and glorious excess in 1970's Paris - Drake, Alicia (Back Bay Books, 2007)
"In the 1970's, Paris fashion exploded like a champagne bottle left out in the sun. Amid sequins and longing, celebrities and aspirants flocked to the heart of chic, and Paris became a hothouse of revelry, intrigue, and searing ambition. At the center of it all were fashion's most beloved luminaries - Yves Saint Laurent, the enfant terrible, and Karl Lagerfeld, the flamboyant freelancer with a talent for reinvention - and they divided Paris into two fabulous halves. Their enduring rivalry is chronicled in this dazzling exposé of an era: of social ambitions, shared obsessions, and the mesmerizing quest for beauty."--Publisher description.